Ketamine Use for Tracheal Intubation in Critically Ill Children Is Associated With a Lower Occurrence of Adverse Hemodynamic Events. Issue 6 (June 2020) - Conway, J. Arden; Kharayat, Priyanka; Sanders, Ronald C.; Nett, Sholeen; Weiss, Scott L.; Edwards, Lauren R.; Breuer, Ryan; Kirby, Aileen; Krawiec, Conrad; Page-Goertz, Christopher; Polikoff, Lee; Turner, David A.; et al.
Abstract : Objectives: Tracheal intubation in critically ill children with shock poses a risk of hemodynamic compromise. Ketamine has been considered the drug of choice for induction in these patients, but limited data exist. We investigated whether the administration of ketamine for tracheal intubation in critically ill children with or without shock was associated with fewer adverse hemodynamic events compared with other induction agents. We also investigated if there was a dose dependence for any association between ketamine use and adverse hemodynamic events. Design: We performed a retrospective analysis using prospectively collected observational data from the National Emergency Airway Registry for Children database from 2013 to 2017. Setting: Forty international PICUs participating in the National Emergency Airway Registry for Children. Patients: Critically ill children 0–17 years old who underwent tracheal intubation in a PICU. Interventions: None. Measurements and Main Results: The association between ketamine exposure as an induction agent and the occurrence of adverse hemodynamic events during tracheal intubation including dysrhythmia, hypotension, and cardiac arrest was evaluated. We used multivariable logistic regression to account for patient, provider, and practice factors with robust SEs to account for clustering by sites. Of 10, 750 tracheal intubations, 32.0% ( n = 3, 436) included ketamine as an induction agent. The most common diagnoses associated with ketamine use were sepsis and/or shock (49.7%). After adjusting for potential confounders and sites, ketamine use was associated with fewer hemodynamic tracheal intubation associated adverse events compared with other agents (adjusted odds ratio, 0.74; 95% CI, 0.58–0.95). The interaction term between ketamine use and indication for shock was not significant ( p = 0.11), indicating ketamine effect to prevent hemodynamic adverse events is consistent in children with or without shock. Conclusions: Ketamine use for tracheal intubation is associated with fewer hemodynamic tracheal intubation–associated adverse events. Abstract : Supplemental Digital Content is available in the text.